Evaluation of tear function tests and corneal thickness in patients with meibomian gland dysfunction - Teberik, Kuddusi; İritas, İlter (The European Research Journal, 2020)
Objectives: To investigate whether central corneal thickness (CCT) and tear function test differ from healthy controls in the ones suffering meibomian gland dysfunction (MGD). Methods: This prospective study was carried out with 99 individuals in total (50 patients MGD, 49 healthy individuals). Schirmer-1, tear break-up time (TBUT), the Ocular Surface Disease Index (OSDI) questionnaire and CCT measurmentwas administered to all patients. Results: The average Schirmer 1 measurements were 16.6 ± 3.3 mm for right eyes, 16.4 ± 3.6 mm for left eyes in the MGD group and 17.1 ± 3.7 mm for right eyes, 17.0 ± 4.4 mm for left eyes in the control group. The mean TBUT values were 10.1 ± 3.6 seconds for right eyes, 10.2 ± 3.4 seconds for left eyes in the MGD group and 14.7±3.7 seconds for right eyes, 15.8 ± 4.1 seconds for left eyes in the control group (p = 0.001). The mean OSDI score values were 40.3 ± 23.7 in the MGD group and 19.4 ± 8.7 in the control group (p = 0.001). The average CCT in the MGD group was 539.4 ± 30.0 µm and 539.7 ± 33.0 µm (right and left, respectively). The average CCT in the control group was 551.6 ± 32.8 µm and 550.7 ± 32.2 µm (right and left, respectively). The mean CCT measurements in the MGD group were not statistically significant compared to the healthy control group (p = 0.059, and p = 0.097, right and left, respectively). Conclusions: The Schirmer test and CCT measurements are not significantly different in patients with MGD compared to healthy control subjects.